Neural circuit mechanisms of acupuncture effect: where are we now? - Wang, Xuesong; Wang, Jia; Han, Rui; Yu, Chaochao; Shen, Feng (Frontiers in Neurology, 2024)
Recently, there has been increasing attention on the impact of acupuncture on the dysregulated neural circuits in different disease. This has led to new understandings of how acupuncture works. This review presents a comprehensive analysis of research that have examined the impact of acupuncture on abnormal neural circuits associated with pain, anxiety, Parkinson’s disease, addiction disorders, cognitive problems, and gastrointestinal disorders. These studies have shown that acupuncture’s therapeutic effects are mediated by specific brain areas and neurons involved in neural circuit mechanisms, emphasising its wide-ranging influence. The positive impacts of acupuncture can be ascribed to its ability to modify the functioning of neurocircuits in various physiological conditions. Nevertheless, contemporary studies on acupuncture neural circuits frequently overlook the comprehensive circuit mechanism including the periphery, central nervous system, and target organ. Additionally, the scope of diseases studied is restricted. Future study should focus on broadening the range of diseases studied and exploring the neural circuit mechanisms of these diseases in depth in order to enhance our understanding of acupuncture’s neurobiological impacts.